Kinematics and thermodynamics of a midlatitude, continental mesoscale convective system and its mesoscale vortex - Knievel, Jason C., author (Colorado State University. Libraries, 2002)
The author examines a mesoscale convective system (MCS) and the mesoscale convective vortex (MCV) it generated. The MCS, which comprised a leading convective line and trailing stratiform region, traversed Kansas and Oklahoma on 1 August 1996, passing through the NOAA Wind Profiler Network, as well as four sites from which soundings were being taken every three hours during a field project. The unusually rich data set permitted study of the MCS and MCV over nine hours on scales between those of operational rawinsondes and Doppler radars. The author used a spatial bandpass filter to divide observed wind into synoptic and mesoscale components. The environment-relative, mesoscale wind contained an up- and downdraft and divergent outflows in the lower and upper troposphere. The mesoscale wind was asymmetric about the MCS, consistent with studies of gravity waves generated by heating typical of that in many MCSs. According to a scale-discriminating vorticity budget, both the synoptic and mesoscale winds contributed to the prominent resolved sources of vorticity in the MCV: tilting and convergence. Unresolved sources were also large. The author speculates that an abrupt change in the main source of vorticity in an MCV may appear as an abrupt change in its altitude of maximum vorticity. Distributions of temperature and humidity in the MCS were consistent with its mesoscale circulations. In the terminus of the mesoscale downdraft, advection of drier, potentially warmer air exceeded humidifying and cooling from rain, so profiles of temperature and dewpoint exhibit onion and double-onion patterns. The mesoscale updraft was approximately saturated with a moist adiabatic lapse rate. Mesoscale drafts. and convective drafts vertically mixed the troposphere, partially homogenizing equivalent potential temperature. The MCV contained a column of high potential vorticity in the middle troposphere, with a cold core below the freezing level and a warm core above-a pattern characteristic of profiles of heating by stratiform regions. The cold core was 2 km too shall w to be in pure gradient balance with wind in the MCV. Ongoing forcing during the observed lifetime of the MCV may have prevented it from achieving balance, even if that was its tendency.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 2001.
Keywords: Convection (Meteorology); Vortex-motion